TINJAUAN HUKUM ISLAM TERHADAP LARANGAN KAWIN SASUKU DI MASYARAKAT MINANGKABAU - Nurchaliza, Vidya (Journal of Islamic Law Studies, 2020)
Customs in Minangkabau are known as customs that are along with Islamic norms. Almost all cultures in Minangkabau are Islamic teachings that are followed by the majority of the Minangkabau people. However, there is one custom that causes polemic in the community, namely the prohibition of marriage of Sasuku. Whereas in Islamic Law there are no prohibition of marriage with one tribe. On the other hand, according to Indonesian marriage law, a legal marriage is a marriage made according to the religion and beliefs of the bride and groom. This research was conducted using the normative juridical method of secondary data relating to marriage in adat Minangkabau and marriage in Islam. This paper aims to find the right perspective on the culture of prohibition of marriage of Sasuku in the Minangkabau community based on the principles of marriage in Islamic law. The results showed that in the perspective of Islamic law, the prohibition of marriage of Sasuku was basically permissible because of the avoidance of marriages arising from marriage that is causing bad heredity. The prohibition is also in line with the objective of Islamic Law (maqashid syariah), namely to maintain offspring.